Complex variable treatment of bending of micropolar plates - Constanda, C.
In this paper the linear non-homogeneous equations of equilibrium of the bending of micropolar plates are integrated in terms of complex potentials. Conditions for the uniformity of the displacements, microrotations, stresses and micromoments are also given. In the last section the problem of the bending of an infinite plate with a circular hole is solved by means of the formulae previously derived.
Keywords: STRUCTURAL ANALYSIS - MATHEMATICAL MODELS